THE HIDDEN MEANING OF HYPERBOLE USED IN THE SONG LYRIC OF JUSTIN BIEBER’S ALBUM “CHANGES” - Narsiana Lesti Hawung (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This research discusses about hyperbole that is used in the song lyric of Justin Bieber's album “changes”. The objective of this study is to understand the hyperbole based on the theory by Knickerbocker and Reninger,(1963:367) and analyzed the meaning based on the theory by Leech (1974:10), that used in the song lyrics of Justin Bieber album "Changes". In collecting the data, the writer used the observation method. The data collection was conducted by some steps, such are: (1) Listening to the song lyrics from the website www.genius.com, (2) reading the song carefully, (3) Highlight the sentence that has hyperbole, and analyze the meaning of each hyperbole that is used in the song lyrics of Justin Bieber's album "Changes". In this study, the writer used the qualitative research method. There are two theories conducted in this study: Firstly, the writer identify the data that has hyperbole by using the theory by Knickerbocker and Reninger (1963:367). Secondly, the writer analyzed the meaning that found in hyperbole by the theory of Leech (1974:10) that used in the song lyrics. The total of hyperbole found in Changes album by Justin Bieber was 5 data there are two meaning found, such are: connotative meaning with occurrence 2 and 33,33% of percentage, and affective meaning with occurrence 4 and 66,67% of percentage. The dominant meaning of hyperbole that used in the song lyrics of Justin Bieber album “Changes” is affective meaning with the occurrence 4 and 66,67% of percentage.